Strengthening Character Education through the Development of Picture Story Book Based on Local Wisdom - Jannah, Raudlatul (Departemen Pendidikan Guru Madrasah Ibtidaiyah Fakultas Tarbiyah dan Keguruan Universitas Islam Negeri Antasari Banjarmasin, 2025)
This study aims to develop a picture storybook based on the local wisdom of Song Osong Lombhung (cooperative character) and determine the effectiveness of its use. This research uses a Research and Development (R&D) approach using the ADDIE development model. The participants comprised 17 fourth-grade students from MI Al-Azhar. Data were collected through expert validation questionnaires, student response questionnaires, and pre-test and post-test assessments. The expert validation results indicated a high level of validity, with an average score of 91.3%, categorizing the product as highly feasible. Student responses also demonstrated a positive reception, with an attractiveness rating of 81.8%. Furthermore, statistical analysis revealed significant improvement in students' cooperative behavior, with the average post-test score increasing from 68.3 to 84.7. The N-Gain score of 59.8% indicated a moderate level of effectiveness. The findings suggest that the developed picture storybook is appropriate and effective in enhancing cooperative character education, integrating local cultural values relevant to the student's socio-cultural environment.